(untitled) (Experimental biology, 2025)
The article presents the results of the study of the genus Eremurus of the family Asphodelaceae, which includes more than 70 species of perennial grasses with thickened roots and root leaves. According to «Flora of Kazakhstan», 13 species of the genus are registered in Kazakhstan, but according to M.S. Baitenov, their number reaches 15 species. Literature sources were screened and more than 130 herbarium specimens from major collections (AA, TASH, LE, MW) from 1988 to 2024 were reviewed. We have determined the ranges of the studied species according to the Botanical-geographical zoning of Kazakhstan and Central Asia: Eremurus robustus has the following range: Region - Saharo-Gobian, Subregion - Irano-Turanian, Province - Mountain-middle - Asian - Dzungarian - Dzungaro-North Tianshanian; Eremurus tianschanicus has the following range: Region - Saharo-Gobian, Subregion - Irano-Turanian, Province - Mountain-middle - Asian - Dzungaro-North Tianshanian.